Reforestation for environmental services as valued by local communities: a case study from Lebanon - Amidi, Juliette; Stephan, Jean Mikhael; Maatouk, Elias (Forestry economics review, 2020)
PurposeLebanon has been subject to important reforestation activities which resulted in the establishment of several cedars, pine and other mixed forest stands on communal lands. These stands are not designated for timber production but rather for nonwood forest products (NWFPs), landscape restoration and for environmental services. The study aims at valuating old reforested sites from the perspective of rural communities neighboring those reforested stands.Design/methodology/approachTo assess the non-timber goods and services provided by these forest ecosystems, 13 reforested sites located in different regions in Lebanon were selected. The socioeconomic assessment was done using questionnaires distributed to locals that have close interactions with the neighboring forests; it included, among others, a double-bonded dichotomous contingent valuation (CV) related to their willingness to pay (WTP) for reforestation and forest management activities.FindingsResults of the goods and services assessment revealed that the forests have multifunctional uses with ecotourism as a major activity in all forest types. The CV showed that 75% of respondents did express a WTP. Most of the respondents did so, thus giving a great importance to intrinsic values of the forests. Lower income did not negatively affect the WTP of respondents but rather age and the educational level did. Other factors such as forest type, forest surface and the biodiversity status of the sites did not have an impact on WTP.Practical implicationsThese results are very informative for governmental policies seeking funds to perform reforestation programs for environmental objectives, involving local communities in co-funding these programs would help insure the sustainable conservation of reforestation sites.Social implicationsDespite their relative low income, poor communities are willing to pay to sustain forests and their ecosystem services.Originality/valueIt is the first time that a CV is used for ecosystem services regenerated from 50–60 years old reforested sites in a semiarid region, where trees are not planted for timber production. It is one of the few examples were lower income did not affect the WTP for forests providing environmental services on communal lands.